The patient‐reported disease burden in adults with atopic dermatitis: a cross‐sectional study in Europe and Canada. (14th January 2020) - de Bruin‐Weller, M.; Gadkari, A.; Auziere, S.; Simpson, E.L.; Puig, L.; Barbarot, S.; Girolomoni, G.; Papp, K.; Pink, A.E.; Saba, G.; Werfel, T.; Eckert, L.
Abstract: Background: Cross‐sectional data on patient burden in adults with atopic dermatitis (AD) from real‐world clinical practice are limited. Objective: This study compared patient‐reported burden associated with adult AD across severity levels from clinical practices in Canada and Europe. Methods: This study included adults (18–65 years) diagnosed with AD by dermatologists, general practitioners or allergists. Participants categorized as mild ( n = 547; 37.3%), moderate ( n = 520; 35.4%) or severe ( n = 400; 27.3%) based on Investigator's Global Assessment completed a questionnaire that included pruritus and pain numerical rating scales, Patient‐Oriented‐Scoring of Atopic Dermatitis (PO‐SCORAD) itch and sleep visual analogue scales, Dermatology Life Quality Index (DLQI), and the Hospital Anxiety and Depression Scale (HADS). Participants were also stratified by inadequate efficacy/intolerance/contraindication to cyclosporine [Cyclo; n = 62 (4 mild, 18 moderate, 40 severe)] and any systemic immunomodulatory agent [IMM; n = 104 (13 mild, 31 moderate, 60 severe)] and compared with the severe group excluding participants identified as Cyclo/IMM. Results: Age was similar across severity groups; the proportion of women was higher in the mild group relative to severe (61.2% vs. 50.5%; P < 0.001). Compared with moderate and mild, participants with severe AD had more comorbidities, higher itch and pain severity, worse sleep and higher levels of anxiety and depression (all P < 0.001). Mean ± SD DLQI score among participants with severe AD (16.2 ± 6.9) showed a large effect on quality of life that was higher than those with moderate (10.2 ± 6.3) and mild (5.5 ± 4.9) (both P < 0.001). The burden among Cyclo and IMM subgroups was generally similar to that of participants with severe AD. Conclusions: Adults with AD reported a substantial burden across multiple domains that was significantly higher in those with severe disease. The burden among participants in the Cyclo/IMM subgroups was similar to those with severe AD.